A million and more trees for science - Paquette, A; Hector, A; Castagneyrol, B; Vanhellemont, M; Koricheva, J; Scherer-Lorenzen, M; Verheyen, K; TreeDivNet (Springer Nature, 2018)
TreeDivNet is the largest network of biodiversity experiments worldwide, but needs to expand. We encourage colleagues to establish new experiments on the relation between tree species diversity and forest ecosystem functioning, and to make use of the platform for collaborative research.